Elektronischer Handel im Lichte der Bestreitbarkeit von Märkten - Stefan Mai; Mark Oelmann (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2001)
Information and communication technologies are transforming economies and societies around the world. In this respect, E-Commerce has the capability to build a new global economy. That is why government, industries, non-profit-organisations, trade unions and consumers would like to come together to set up a regulatory framework. As set out in our paper competition effects have to be considered when doing so. We identify and discuss various regulatory and private entry barriers to electronic markets and answer the question whether or not there is any need for international policy coordination in E-Commerce.
Keywords: H1; L10; L50; 330; E-Commerce; Competition; Regulation; E-Business; Markteintritt; Potenzieller Wettbewerb; Network Externalities; Wettbewerbspolitik; Internationale wirtschaftspolitische Koordination; Theorie; Welt